How Do People With Intellectual Disability Engage With and Understand Gambling? A Qualitative Study of Adults in Victoria, Australia - Pitt, Hannah; Thomas, Samantha L.; Watson, Joanne; Shuttleworth, Russell; Murfitt, Kevin; Balandin, Susan (Frontiers in Public Health, 2021)
Objective This study aimed to understand the factors that may influence how and why people with intellectual disability may engage in gambling. Method Nineteen people with intellectual disability were recruited from a disability advocacy organisation and participated in face to face, semi-structured qualitative interviews. Open ended questions were used to explore participants’ gambling participation, recall of, and attitudes towards, different gambling products, understanding of gambling harm, and awareness of responsible gambling messages. Results All participants could remember gambling in their lifetime and some participants had recently engaged in gambling. Many participants were aware of different gambling products, and a few participants could describe in detail the technical aspects of electronic gambling machines. Most participants did not specifically recall seeing gambling harm minimisation messages, however some described engaging in individual responsibility measures, such as limits and control, as they perceived this reduced the risks of experiencing harm. Conclusions People with intellectual disability are engaging with gambling products in a similar way to the general community. Therefore, it is important to understand the different pathways that may lead people with lifelong disability to initiate and continue gambling and to ensure that they are aware of and protected from the potential risk. Implications for public health Policy makers and practitioners should seek to understand and implement a range of strategies to reduce and prevent the harms associated with particular gambling products and environments for this population sub-group.